Winter‐time variability of the eastern Arabian Sea: A comparison between 2003 and 2013. Issue 12 (17th June 2017) - Narvekar, Jayu; D'Mello, Joshua Rosario; Prasanna Kumar, S.; Banerjee, Priyanka; Sharma, Vrinda; Shenai‐Tirodkar, Prachi
Abstract: The eastern Arabian Sea (EAS) is a region of complex interplay between several spatially and temporally varying oceanographic processes. Using two sets of in situ data collected from the same stations, separated by a decade, we show that warming and cooling in the EAS were linked to the long‐term variability of this region. Though the warming in the southern part of EAS was consistent with the basin‐wide rise in sea surface temperature in the Arabian Sea (AS), the enhanced freshening was a remote response to episodic events mediated by the strengthening of interbasin exchange between Bay of Bengal and AS through East India Coastal Current and West India Coastal Current. The increased stratification in the southern part of EAS led to the decline in the chlorophyll over the decade. In contrast, enhanced chlorophyll in the northern part of the EAS over the decade was linked to the increased wind speed. Key Points: Differential winter‐time response of eastern Arabian Sea in recent decade was explored to unravel the ocean processes Warming and declining chlorophyll in the southern part of eastern Arabian Sea mediated by remotely controlled freshening events Enhanced interbasin exchange via boundary current contributed to the increased stratification